Combinatory optimization of chromosomal integrated mevalonate pathway for β-carotene production in Escherichia coli. Issue 1 (December 2016) - Ye, Lijun; Zhang, Chunzhi; Bi, Changhao; Li, Qingyan; Zhang, Xueli
Abstract Background Plasmid expression is a popular method in studies of MVA pathway for isoprenoid production inEscherichia coli . However, heterologous gene expression with plasmid is often not stable and might burden growth of host cells, decreases cell mass and product yield. In this study, MVA pathway was divided into three modules, and two heterologous modules were integrated into theE. coli chromosome. These modules were individually modulated with regulatory parts to optimize efficiency of the pathway in terms of downstream isoprenoid production. Results MVA pathway modulesHmg1 -erg12 operon andmvaS -mvaA -mavD1 operon were integrated intoE. coli chromosome followed by modulation with promoters with varied strength. Along with activation ofatoB, a 26% increase of β-carotene production with no effect on cell growth was obtained. With a combinatory modulation of two key enzymesmvas andHmg1 with degenerate RBS library, β-carotene showed a further increase of 51%. Conclusions Our study provides a novel strategy for improving production of a target compound through integration and modulation of heterologous pathways in both transcription and translation level. In addition, a genetically hard-coded chassis with both efficient MEP and MVA pathways for isoprenoid precursor supply was constructed in this work.